Selectivity of the oriental fruit moth sex pheromone trap in peach and apricot orchards - Hári, K.; Pénzes, B. (International Journal of Horticultural Science, 2010)
One of the most important pests of the stone fruit orchards is the oriental fruit moth (Grapholitha 1110/esta B.). Chemical control targeted against the young larvae is the most effective way of protection. so the ti ming of treatments has to be based on the observation of emergence. Emergence may be monitored with sex pheromone traps. It is already known from former publications, that the traps for oriental fruit moth are also effective in the case of the plum moth (Grapholitha f1111ebra11a Tr.), which external morphology is very similar to the oriental fruit moth. As the emergence of the oriental fruit moth in peach and apricot orchards has not been observed in detaib in Hungary, we started a s1Udy in this field. Our aim was to measure the selectivity of the sex pheromone traps. On the basis of examining more than 5000 males caught and the investigation of male genital ia. it could be established that the pheromone traps. Csalomon and Deltastop, for oriental fruit moth, caught the plum moth in the same ratio. The ratio of the oriental fruit moth and the plum moth trapped in the peach orchards was I: I . while in the apricot orchards the number of the caught plum moth males was seven times as many as that of the oriental fruit moths. Consequently, it can be established that data based on oriental fruit moth trap catches can not be used without additional investigations of genitalia for the prediction of larval hatch. The selectivity of the plum moth trap. used as a control. was acceptable in both orchards.